The Role of Family in The Formation of LGBT Identity - Fatimah, Sarah Nurul; Nurillah, Amelia Fikri (Universitas Pendidikan Indonesia (UPI), 2025)
This study aims to examine in depth the role of family in the formation of LGBT identity through a literature review approach. An individual's sexual and gender identity is formed through a long process influenced by various factors, one of which is the family environment, as the primary foundation of self-development from an early age. A harmonious and affectionate family with open communication patterns has been proven to positively shape a child’s gender identity. Conversely, family disharmony, unbalanced parenting, the absence of parental figures, and the lack of character and sexual education within the family can increase the risk of identity confusion in children and make them more vulnerable to seekinadsg validation outside the family environment. This study analyzes scientific articles that discuss the relationship between family dynamics and LGBT identity, which are then categorized into several main themes, such as parenting patterns, emotional attachment, education within the family, and family-based interventions. The results of this review are expected to serve as a foundation for designing prevention and assistance strategies based on family involvement to support the healthy development of children's sexual and gender identity, following Indonesian social and cultural values.